Counseling Challenges in the New Normal : Inputs for Quality Guidance and Counseling Program - Arrieta, Gilbert S; Valeria, John Remwil; Belen, Von Ryan (Universitas PGRI Madiun, 2021)
With no face-to-face classes until a vaccine is available, schools have to adjust and learning must continue in different modalities. In the Philippines, online learning delivery is the primary mode of learning with many private schools adapting it. Learning continuity plan was created and the Department of Education set the most essential learning competencies for school year 2020-2021. Since education is a holistic approach, the mental and emotional well-being of the students must also be given significant attention. Counseling, a strong support in the welfare of the students, is needed to address the different concerns of the students. However, guidance counselors see a lot of challenges in providing counseling to students in an online environment. They have doubts in being truly present with the students. Potential mental and emotional health issues have been identified and preparations were made that will make the guidance and counseling services more felt and reliable despite being in an online modality. This study aims to find out the challenges that the guidance counselors encountered in providing counseling service to students. It also aims to identify the issues and concerns experienced by the students in online learning and the interventions provided by the guidance counselors in handling them. It found out that mental health issues, feeling of isolation, voluminous requirements and unstable internet connection were the concerns of the students. In addressing them, they provided individual and group counseling, communicated with the parents, collaborated more closely with the class advisers, teachers, and academic heads, strengthened the homeroom and guidance period, and held mental health activities. From the experiences, their realizations and new gained insights will be used as bases in enhancing the guidance and counseling program for school year 2021-2022.